Trade, Politics, and Revolution : South Carolina and Britain's Atlantic Commerce, 1730-1790 - David, Huw T., 1981- (Book collections on Project MUSE., 2018)
A study of early transatlantic trade in South Carolina that exposes the divisive complexity that led to war.